Temporal target restriction of olfactory receptor neurons by Semaphorin-1a/PlexinA-mediated axon-axon interactions. - Sweeney, L.B.; Couto, A.; Chou, Y.H.; Berdnik, D.; Dickson, B.J.; Luo, L.; Komiyama, T. (Neuron, 2007)
Axon-axon interactions have been implicated in neural circuit assembly, but the underlying mechanisms are poorly understood. Here, we show that in the Drosophila antennal lobe, early-arriving axons of olfactory receptor neurons (ORNs) from the antenna are required for the proper targeting of late-arriving ORN axons from the maxillary palp (MP). Semaphorin-1a is required for targeting of all MP but only half of the antennal ORN classes examined. Sema-1a acts nonautonomously to control ORN axon-axon interactions, in contrast to its cell-autonomous function in olfactory projection neurons. Phenotypic and genetic interaction analyses implicate PlexinA as the Sema-1a receptor in ORN targeting. Sema-1a on antennal ORN axons is required for correct targeting of MP axons within the antennal lobe, while interactions amongst MP axons facilitate their entry into the antennal lobe. We propose that Sema-1a/PlexinA-mediated repulsion provides a mechanism by which early-arriving ORN axons constrain the target choices of late-arriving axons.